MISC Berhad: Investable Growth With The Blue Ocean Strategy - Loh, Chee Can (2008)
MISC Berhad MISC), a subsidiary of Petrolium Nasional Berhad (Petronas), was established in 1968 and is the leading international shipping line of Malaysia. The principal business of MISC Berhad consists of ship-owning, ship management, maritime transportation services. The study on the blue ocean strategies provide a systematic approach in creating an uncontested market space and making the value innovation to MISC Berhad journey to becoming 'the preferred provider of world-class maritime transportation and logistics services", on its three core pillars of global energy shipping, capability driven heavy engineering services and ASEAN centric logistics services.